A Zr-doped single-phase Pt-modified aluminide coating and the enhanced hot corrosion resistance. (1st April 2018) - Jiang, C.Y.; Yang, Y.F.; Zhang, Z.Y.; Bao, Z.B.; Chen, M.H.; Zhu, S.L.; Wang, F.H.
Highlights: Single-phase Zr-doped β-(Ni, Pt)Al coating is prepared by Pt-Zr electroplating and aluminisation. With Pt/Zr modification, hot corrosion resistance of plain NiAl coating is notably improved. After 200 h, Cr-rich belt is observed in accordance with Cl in deeper (Ni, Pt)Al coating. Zr fixes and stabilises S at surface, capable of inhibiting presence of S at OZ/IDZ interface. Internal chlorination, which occurs in normal (Ni, Pt)Al, is absent in Zr-doped (Ni, Pt)Al coating. Abstract: A Zr-doped single-phase (Ni, Pt)Al coating was prepared on a Ni-based single crystal superalloy through electroplating Pt-Zr composite layer and subsequent gaseous aluminisation treatments. Hot corrosion tests of simple aluminide, (Ni, Pt)Al and Zr-doped (Ni, Pt)Al coatings in Na2 SO4 /NaCl (75:25, wt./wt.) were conducted at 850 °C in static air. The results indicated that the Zr-doped coating showed superior hot corrosion resistance to both conventional aluminide and (Ni, Pt)Al coatings, in which the enhanced performance is mainly attributed to the advantageous effects of Zr that interacts with S and Cl. The mechanism and role of Zr played in the corrosion test are discussed.